Climate impact of Finnish air pollutants and greenhouse gases using multiple emission metrics - Kupiainen, Kaarle Juhana; Aamaas, Borgar; Savolahti, Mikko; Karvosenoja, Niko; Paunu, Ville-Veikko (Atmospheric Chemistry and Physics, 2022)
We present a case study where emission metric values from different studies are applied to estimate global and Arctic temperature impacts of emissions from a northern European country. This study assesses the climate impact of Finnish air pollutants and greenhouse gas emissions from 2000 to 2010, as well as future emissions until 2030. We consider both emission pulses and emission scenarios. The pollutants included are SO2, NOx, NH3, non-methane volatile organic compound (NMVOC), black carbon (BC), organic carbon (OC), CO, CO2, CH4 and N2O, and our study is the first one for Finland to include all of them in one coherent dataset. These pollutants have different atmospheric lifetimes and influence the climate differently; hence, we look at different climate metrics and time horizons. The study uses the global warming potential (GWP and GWP*), the global temperature change potential (GTP) and the regional temperature change potential (RTP) with different timescales for estimating the climate impacts by species and sectors globally and in the Arctic. We compare the climate impacts of emissions occurring in winter and summer. This assessment is an example of how the climate impact of emissions from small countries and sources can be estimated, as it is challenging to use climate models to study the climate effect of national policies in a multi-pollutant situation. Our methods are applicable to other countries and regions and present a practical tool to analyze the climate impacts in multiple dimensions, such as assessing different sectors and mitigation measures. While our study focuses on short-lived climate forcers, we found that the CO2 emissions have the most significant climate impact, and the significance increases over longer time horizons. In the short term, emissions of especially CH4 and BC played an important role as well. The warming impact of BC emissions is enhanced during winter. Many metric choices are available, but our findings hold for most choices.